77 Inhalers for COPD have a measurable effect but do they really work?. (8th June 2022) - Falk, Jamie; McCormack, James
Abstract : Currently more than 20 inhalers are approved for the management of COPD and marketed in North America. About half are single medication inhalers and half are combination medication inhalers. This abundance of inhalers leaves many clinicians and patients confused and wondering which inhaler, if any, to add and how to make that decision. When making decisions about inhalers, clinicians should focus on the best available evidence around outcomes which are clinically relevant to patients. Although clinical trials may show statistically significant differences on clinically relevant outcomes, this doesn't necessarily mean the magnitude of these differences would be considered clinically meaningful to an individual patient or clinician. To practice in an evidence-based fashion clinicians need to have an understanding of the ballpark chance an individual patient will get a clinically meaningful effect from any specific inhaler and, if possible identify if, in fact, a specific patient is getting a clinically important effect on their symptoms from a specific inhaler once it has been started. As of late 2018, multiple meta-analyses have been published outlining benefits and harms of triple therapy (LAMA/LABA/ICS) versus dual therapy (LAMA/LABA) in the management of COPD. In this session, using these meta-analyses and their individual clinical trial data, we'll take an in-depth look at the magnitude of the benefits and harms attributed to these inhalers and the potential ways to use this evidence clinically. Through the use of absolute risk differences, changes in dyspnea and quality of life scores, minimum clinically important differences, and responder analyses, we'll walk through how meta-analysis and individual trial outcomes data can be translated into usable presentations of the potential positive and negative impacts inhalers have on clinically relevant COPD outcomes. In addition we'll address how this evidence can be used to clinically monitor patients once they are on inhalers for COPD. Appreciating the challenges of applying often relatively small clinical outcome changes that inhalers provide to decision making in a condition that has a relatively larger fluctuating and dynamic symptomatology, participants will consider the pros and cons of several approaches to the clinical monitoring of patients with COPD. Objectives: Understand the importance of the clinical relevance of COPD outcomes in individual patient decisions. Integrate the use of clinical outcome data into translatable information for shared decision making. Appreciate and work within the challenges of how to apply clinical outcome data in a condition that is consistently fluctuating.